(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Irregular sleep patterns are increasingly prevalent among university students and are associated with metabolic disturbances, impaired recovery, and changes in body weight. This study aimed to analyze the impact of sleep patterns—including sleep onset time, wake-up time, sleep duration, sleep quality, and sleep schedule consistency—on the body weight of students in the Sports Coaching Education Study Program at Universitas Pejuang Republik Indonesia (UPRI). This research employed a quantitative correlational approach with a cross-sectional design. A total of 80 active students were selected using purposive sampling techniques. Sleep data were collected using the Pittsburgh Sleep Quality Index (PSQI) questionnaire and a 28-day sleep diary, while anthropometric measurements were used to determine Body Mass Index (BMI). Data analysis utilized Pearson correlation and stepwise multiple linear regression tests. The findings revealed that the average sleep duration of students was 6.24 hours per night, indicating insufficient sleep according to recommended standards. Correlation analysis demonstrated that short sleep duration was significantly associated with increased BMI (r = -0.62; p < 0.001). Late bedtime (r = 0.54; p < 0.001), poor sleep quality measured by PSQI (r = 0.57; p < 0.001), and social jetlag (r = 0.49; p < 0.001) were also significantly correlated with higher BMI. Multiple regression analysis showed that sleep duration, sleep quality, and bedtime collectively explained 58.4% of BMI variance. In conclusion, multidimensional sleep behavior significantly influences body weight among sports coaching students, emphasizing the importance of sleep hygiene interventions within student wellness and sports education programs.